O uso do cortisol salivar no teste da desmopressina na doença de Cushing e na obesidade - Ricardo Mundim Firme (2017)
Cushing's disease is still an important diagnostic and therapeutic challenge, as well as showing very high morbidity and mortality. Primary obesity, a worldwide epidemic, is increasingly present in this arduous differential diagnosis. The classic desmopressin test, with serum cortisol and ACTH measurements after venous administration of 10mcg of desmopressin, has been shown to have excellent accuracy in the context of exclusion of Cushing's syndrome in patients with nontumoral hypercortisolism; this occurs with a quality equal to or greater than the synthetic corticotrophin (CRH) test. Salivary cortisol was added to the classic test, and 19 individuals from specific outpatient clinics of the UFMG medical school were added to the test: 11 patients with active Cushing's disease (group A) and 08 individuals with moderate to severe obesity (BMI greater than 35kg / m2 - group B). All patients in the first group were submitted to current criteria of hypercortisolism activity and obese patients were excluded from this initial laboratory change. The groups were clinically homogeneous, but with an important difference in descriptive parameters and statistical tests. Significant differences were observed in intragroup analyzes (Anova Two way multiple analyzes, p <0.05) and intergroup (p <0.01); it was observed that in group A an increase of salivary cortisol in relation to basal (increases of 66 to 309%), and a strong positive correlation between salivary cortisol and serum cortisol in some (45, 60,120 minutes) in Cushing disease group. The addition of salivary cortisol to the dynamic test is well indicated in the current context of neuroendocrinology, may after future analysis add diagnostic accuracy and even simplify the dynamic test. A larger, more diverse and multicentric population should be analyzed and more robust data obtained.